(untitled) (Nigerian Journal of Technology, 2024)
The railway track’s sub-ballast layer is important, but it is often neglected, leading to the contamination and blockage of voids, as well as track deformation and degradation. These issues occur when fouling materials infiltrate the sub-ballast due to load-induced vibration. The purposes of this paper are to investigate the influence of vibration on the sub-ballast layer when loads are applied to a fouled ballast and to determine whether sub-ballast saturation should be ignored. A ballast box was fabricated to represent actual railway conditions and filled with 100 kg of ballast aggregates containing fouling materials (crushed ballast, sand, clay, and coal) proportional to the ballast weight. In addition, a vibratory compactor plate machine was used to simulate load on the fouled ballast, inducing vibrations that caused fouling materials to migrate into the sub-ballast. The results indicate that 18% of crushed ballast, 20% of sand, 20.7% of clay, and 15% of coal infiltrated the sub-ballast due to loading-induced vibration, and fouling infiltration percentages rose as vibration from loading increased. These percentages exceeded the standard 10% weight of fouling infiltration into the sub-ballast, indicating an unfavourable sub-ballast condition and showing that sub-ballast saturation should not be ignored. These findings have significant implications for maintenance engineers, as they underscore the need for continuous monitoring and upkeep to ensure optimal sub-ballast performance.